1986
DOI: 10.1203/00006450-198612000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Peptide YY in Human Neonates and Infants

Abstract: ABSTRACT. Plasma concentrations of peptide YY ( P W ) were measured in cord blood and at 6, 12, and 18 days of postnatal life in 24 healthy preterm neonates, from cord blood of eight full-term neonates, and from peripheral blood of 13 infants 9 months old. Concentrations were high in cord blood (73 f 9 pmol/liter versus adult fasting 10.4 f 1.3, p < 0.001) and rose postnatally in the premature infants to 399 f 48 pmol/liter at 6 days, 489 f 42 at 12 days, and fell to 414 f 43 at 18 days. Plasma PYY concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…We found that PYY (3-36) accounted for a high percentage (almost 50%) of total PYY immunoreactivity in our study population, similarly to previous reports in adults (1), and in accordance with the demonstration of both isoforms of PYY, in equal amounts, in fetal intestinal tissues (17). However, it contradicts the results of the study of Adrian et al showing that, on gel permeation chromatography, the majority of circulating PYY-like immunoreactivity, in the neonate, eluted in an identical position to the pure 36 amino acid PYY standard; thus represented the PYY (1-36) (18). As that method was not specific in the detection of the PYY (3-36) isoform, the discrepancy between the results of that study and ours is probably due to the different methodology applied.…”
Section: Discussionsupporting
confidence: 73%
“…We found that PYY (3-36) accounted for a high percentage (almost 50%) of total PYY immunoreactivity in our study population, similarly to previous reports in adults (1), and in accordance with the demonstration of both isoforms of PYY, in equal amounts, in fetal intestinal tissues (17). However, it contradicts the results of the study of Adrian et al showing that, on gel permeation chromatography, the majority of circulating PYY-like immunoreactivity, in the neonate, eluted in an identical position to the pure 36 amino acid PYY standard; thus represented the PYY (1-36) (18). As that method was not specific in the detection of the PYY (3-36) isoform, the discrepancy between the results of that study and ours is probably due to the different methodology applied.…”
Section: Discussionsupporting
confidence: 73%
“…To our knowledge, this is the first study in which circulating concentrations of both PYY and ghrelin were measured in preterm infants and the correlations between these hormones and anthropometric measures, food intake, and growth rates were examined. Circulating PYY concentrations have been measured in a limited number of studies involving preterm infants (17)(18)(19), and the concentrations reported were as high as in our study. Berseth et al (19 ) compared PYY concentrations in preterm and full-term infants and reported higher concentrations in preterm infants, although the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 48%
“…circulating concentrations of PYY were higher at day 12 of life than those observed at day 6 in healthy preterm infants (17 ). Similarly, circulating ghrelin concentrations have been reported to peak after the first postnatal month and up to the 24th month in healthy full-term infants (8 ).…”
Section: Fig 3 Correlations Between Serum Pyy Concentrations and Bmimentioning
confidence: 78%
See 1 more Smart Citation
“…After intestinal resection, glutamine application dramatically increased plasma peptide YY (PYY). It was demonstrated that this increase also leads to increase in tissue PYY content, and thus transit passage time in the intestine shortens and food absorption in the shortened intestines increases (37). It was also shown that PPY functionally damps the discharge of the stomach and extends intestinal passage time after colorectal surgery (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%